Analisis Strategi Pemasaran Digital Mamam Foodies Sukabumi Melalui Akun Instagram @Mamam_Foodies - Agung Prayudha (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
In the digital era, marketing through Instagram has become one of the main strategies to increase brand awareness and customer engagement. Seblak Mamam Foodies has utilized this platform since 2020 with various strategies such as using business accounts, optimizing profiles, and creating engaging content. Features like Instagram Stories, Instagram Live, and Instagram Ads allow direct interaction with customers, strengthening product branding, and increasing competitiveness. Social media not only serves as a communication tool but also as an effective source of information and promotion. This study emphasizes the importance of digital marketing through social media, especially Instagram, in supporting the growth of small and medium-sized enterprises (SMEs) like Seblak Mamam Foodies, by providing insights into successful marketing techniques and their impact on the popularity of the offered products.